فعالية استخدام برنامج تدريبي قائم على اللوغاتم في تحسين الديناميكية عند حبسي بروكا - لعيدات, وداد; حمودي, خيرة (My University, 2020)
Summary : Broca’s Aphasia gathers between three fondamontal symptoms . It is considererd as a non fluent and characterised by a problem in articulation and language production impirement. The purpose from this research is the design of three diffrent chains of logatomes to identify the perfermance of patients suffering from broca’s aphasia and its efficiency in improving the articulation dynamic of this category of patients. In our research, we relied on a case study method and therefore a field applied study was conducted in sidi ali hospital. We have chosen a category of patients on purpose and with appropriate conditions from both sex (male and female). Results were as follow : Broca aphasia patients face problems in applying the right articulation movement of both sounds and letteres while repeating the logatomes. They –the logatomes- were of a great effeciency for the patients since they contributed in the patients preformance and eleminating their troubles through exercising their articulation organs.
Keywords: برنامج تدريبي،اللوغاتم في تحسين الديناميكية،حبسي بروكا